Pengembangan Diversifikasi Olahan Produk Air Nira Bernilai Ekonomis Tinggi di Dusun Kekait Daye - Faresta, Rangga Alif; Septiawan, Adi; Agustina, Sindi Nopita; Zamzami, Zamzami; Karisma, Alan Maulana (Jurnal Pengabdian Masyarakat Sains Indonesia (Indonesian Journal Of Science Community Services), 2020)
NTB is one of the provinces that experienced significant economic growth. In 2017 the economic growth of NTB Province reached 7.1% from 5.6% of national economic growth. Of course this comes from various fields, one of which is the agricultural sector, namely processed products of water sap (palm sugar). The NTB sugar production center is a national superior product commodity with good production quality (NTB in Figures, 2018). One of the villages which is a commodity of palm sugar is Kekait Daye Hamlet. However, this condition is not supported by the earthquake during August-September 2018 which caused the economic paralysis in NTB. The purchasing power of the people has decreased dramatically, the production process of processed products for the people must be stopped and even out of business. So that it causes the production process to weaken because people have to lose production sites and equipment in the manufacture. Plus the products produced are still in the form of general products such as ant sugar and briquette sugar which if sold have prices that are not too high while on the one hand there needs to be innovation to improve the economy of the community. So the researchers made an innovation in the diversification of processed water sap products that have high economic value. This research aims to create processed products of water diversified sap which have high economic value, good packaging and good quality. The method of this research starts from the preparation of tools and materials, making products and socializing to the public. The results of the study were the creation of a diversified process of palm water products in the form of palm sugar, palm coffee , and sugar palm chocolate